Manajemen Pendanaan dan Pendidikan di Pesantren Tarekat Al-Idrisiyyah Tasikmalaya - Yumna Rais; Atikah Atikah; Farida Shabrin Fuadya; Fakhziar Anwar (Journal of Society and Development, 2021)
In the community, Sufism is known as the heart of Islam. In this view, Sufism is often considered to be very close to things that are mysticism. Then many Sufis are also considered an association that focuses more on the piety that exists in each individual than on the piety that is seen in society. This is very different from the Al-Idrisiyyah tarekat, whose students are intended to play a direct role in the community and also play a role in society with other activities. So, in view of the problem formulation, there are two questions: How is the implementation of funding management in the Pesantren Al idrisiyyah Tasikmalaya? and What are the educational programs in the Tasikmalaya Idrisiyah Islamic boarding school? The final results of this study conclude that a tarekat that specializes in its students to contribute directly in the midst of society, the pesantren programs offered are of course related to tarekat, including preaching, education, economy, youth and the role of women.